Analyzing the impacts of industry 4.0 in modern business environments - Brunet-Thornton, Richard, 1953-; Martinez, Felipe, 1976- (IGI Global, 2018)
"This book address the evolution of the current industrial revolutions, a practical and working definition of the concept Industry 4.0, strategic implications of i4.0 implementation, importance of the process improvement in the quest of industry 4.0, consequences of i4.0 adoption for supply chain management, and the Human Resource aspects"- Resumé vydavatel
"Premier reference source"--Cover.
Keywords: management; počítačové sítě; internet věcí; computer networks; Internet of things; sborníky; elektronické knihy; papers of several authors; electronic books